EFEKTIVITAS UNDANG-UNDANG NOMOR 15 TAHUN 2001 TENTANG MEREK TERHADAP DAFTAR MEREK USAHA DAGANG INDUSTRI KECIL DAN MENENGAH - Ukas, Irene Svinarky, Padrisan Jamba (LPPM Universitas Putera Batam, 2017)
Brand role to becomes momentously especially look after healthy effortemulation. Brand momentousing to differentiates a product from porduksame another. That there is rule of law about brand, therefore that brand hasto be listed. Batam's city as business center and industry results variousgoods good product and also service. That product person know that needbrand as distinguishing as of other product that a sort and that there is ruleof law and a moral certaninty rights that didaftarakan shall. This research tosee Number Law effectiveness 15 years 2001 about Brand, in product brandregistration for small enterprise and intermediate. There is method evenresearch that is utilized is observational kualitatif by use of sosiologis'sjudicial formality approaching, which is utilize aught theory and concernsdegan research result at the site. Of research result is known that, stillreducing it / society consciousness understands is of important brandregistration, they don't understand brand registration benefit. Societytendinging to make effort with doesn't list its effort brand, in considerationcost which very expensive eventually sell is not seberapa and there are manyagain another reason, so even aught order insufficiently effective at inpractice it.